Some data of wavelet analysis on the overall dynamics of the dead and recovered during infection COVID-19 - Lyashenko, V.; Eltayib Siddig Mohammed Saad; Asaad Mohammed Ahmed Babker (WJARR, 2020)
Coronaviruses are one of the dangerous sources of human infection. Such a source can be fatal. At the same time, there are certain difficulties in the treatment of diseases that are associated with coronavirus. To solve such issues, it is important to obtain reliable statistics. Equally important is the analysis of the data that are available. Moreover, the necessary condition for the use of such data is the ability to explain the existing relationships between the various parameters that describe the dynamics of the pandemic. The disclosure of these issues is the subject of this study.
Keywords: Viruses; COVID-19; Wavelet analysis; Wavelet coherence